Media Sosial dan Praktik-Praktik Voyeurism - Nadia Sofiyanti; Puji Rianto (Program Studi Ilmu Komunikasi UII, 2021)
Voyeurism is generally understood as deviant sexual behavior. However, it actually covers a wide dimension. The presence of social media makes voyeurism practices more open because of the participatory nature of social media. This study aims to determine the voyeurism in some Yogyakarta student informants related to the motives for doing voyeurism. This study used qualitative research methods. Data collection techniques used in-depth interviews and observation participation on social media. The results revealed several peeping habits, motives and satisfaction when doing voyeurism. Several features on Instagram make it easier for perpetrators to work. Motives are also very diverse. However, the most common is getting sexual gratification from the practice of snooping. In particular, for male actors.